Cechy jakościowe systemu informatycznego w organizacji fraktalnej - Gryncewicz, Wiesława; Moczulski, Michał (Quality of information systems in fractal organisation, 2005)
Global changes in the world are not bound to stop. One answer to this is to adopt a good strategy. Fractal organisations try to achieve this through special characteristics. Information systems play a significant role here but they have to have a suitable level of quality. Widely understood definitions of following aims, availability, friendship towards users, flexibility, efficiency, productivity and currency of information can have a different meaning. The IT solution that is suggested is the intranet as a system which supports the management of communication.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 40-49